Twelve barriers to COPD diagnosis in France: a comparative qualitative study - Maxime Patout; Laurie Fraticelli; Maéva Zysman; Olivier Le Rouzic; Elisabetta Scanferla; Clémence Martin; Mathieu Delorme; Cécilia Nocent-Ejnaini; Guillaume Roucoux; Lize Kiakouama Maleka; Annaig Ozier; Yassine Benarbia; et al. (BMJ Open Respiratory Research)
Background Chronic obstructive pulmonary disease (COPD) is a common treatable disease often diagnosed in patients with risk factors after a prolonged period with suggestive symptoms. Our qualitative study aimed to identify barriers to establishing diagnosis in the natural history of this condition.Methods An inductive thematic analysis was performed on structured interviews with patients, general practitioners (GPs) and pulmonologists in France. Inclusion depended on criteria to generate two purposive samples (patients and physicians). Recruitment occurred online. Data collection proceeded until 15 patients and 15 physicians (eight pulmonologists, seven GPs) were interviewed. Data saturation was checked and achieved. The interviews were transcribed and coded in NVivo and triangulated between two researchers. The article respects the consolidated criteria for reporting qualitative research guidelines.Results Three phases in the patients’ clinical pathway to diagnosis and 12 barriers were found: Phase 1 (symptoms before consultation; n=4), lack of COPD knowledge, symptom denial, fear of lung cancer, and delayed general practice consultations; Phase 2 (primary care; n=3), letting bronchitis become chronic, priority to diseases with similar symptoms and/or more serious diseases, lack of COPD screening devices, time and curative treatments; Phase 3 (specialised medicine; n=5), treatment before diagnosis, late referral to pulmonologists, difficulty in accessing specialists and examination results, patient’s reluctance to undergo further examinations, and need for additional tests to confirm a diagnosis.Conclusion People unaware of their COPD condition can encounter up to 12 barriers, which may combine before obtaining a formal diagnosis. Patients, GPs, pulmonologists and the state health authorities share responsibility for addressing these barriers and enhancing the care pathway.